Analyzing Discourse in The Digital Literacy Contains Pakpak Local Wisdom in Procedure Text in Class - Sagala, Rotama Enjel; Adisaputera, Abdurahman; Dalimunthe, Syairal Fahmi (ppjbsip, 2024)
This research is an analysis related to the application of digital literacy containing Pakpak local wisdom in procedural text material in class VII of SMP Negeri 2 Sumbul. The problems in this research relate to the use of technology and the application of digital literacy containing Pakpak local wisdom in writing procedural texts. The aim of this research is to examine the learning interest and digital literacy of class VII students at SMP Negeri 2 Sumbul. The approach used in this research is a qualitative approach with descriptive analytical research methods. The sample selection in this research was a purposive sample. The research results show that class VII students at SMP Negeri 2 Sumbul have mastered 5 aspects of digital literacy, namely accessing, analyzing and evaluating, creating, reflecting and acting. Students have also been able to process reading related to Pakpak local wisdom and then communicate it to others. It is hoped that the results of this research will be useful for teachers and students, and researchers who wish to conduct similar research related to the application of digital literacy containing Pakpak local wisdom.